The Significance of E-Business and Knowledge- Based Customer Relationship in the E Marketplace Environment - Lai, Joan P.C. (INTI Publishing House Sdn. Bhd., 2006)
Freedom choice and simplicity brought about by e-business and knowledge-based customer relationships are creating the next Internet and mobile wave. The Value Web Technology of enterprise interactions has emerged in the consumer centric world. The combination of evolving business drivers (e.g.: globalization, downsizing), changing customers’ demands and the evolution of enabling technology is producing e-business applications ¡n the e-marketplace environment. The Internet and mobile technology inform an organization that the network offers an opportunity to establish more personal, efficient and competitive relationships with the customers in a new scenario. This paper focuses on the e-marketplace environment and presents some of the findings within an organization using e-business. This organization focuses on the knowledge-based customer relationship as one of the core competency strategies to gain a competitive advantage at the e-marketplace.